ANALISIS TOKOH DAN PENOKOHAN DALAM NOVEL SI ANAK CAHAYA KARYA TERE LIYE - Kelsy Pratiwi; Sesilia Seli; Ahmad Rabi’ul Muzammil (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis research aims to describe the character and support contained in the novel Si Anak Cahaya by Tere Liye, and to know the implementation of character and characterization in the learning process of Bahasa Indonesia high school /MA behavior. The research method used is a descriptive method with a qualitative form of research. The approach used is a structural approach. The source of this research data is the novel The Child of Light by Tere Liye. The techniques and data collection tools used in this study are the study of documenters and researchers themselves. Data validity testing techniques use the persistence of observation, triangulation, and adequacy of references. The results of this study on the character and the support contained in the novel SI Anak Cahaya by Tere Liye on data analysis are carried out by determining the main character and the auxiliary figure as well as the supporting character and the auxiliary figure. The main characters in Tere Liye's novel "The Son of Light" are Nurmas and the auxiliary character Jamilah. The supporting character and supporting character in Tere Liye's novel "The Child of Light" is two ways of portraying the character analytically/directly and Dramatically/indirectly.Keyword : Character, Charaterization, Novel